Comparison of Health-Related Quality of Life Between Ileal Conduit Diversion and Orthotopic Neobladder in Women: A Meta-Analysis - Xing, Wenzhou; Zeng, Sheng; Xu, Zhaoliang; Xing, Shaoqiang; Liu, Qian (Frontiers in Oncology, 2022)
Purpose: To conduct a meta-analysis to explore the comparison of HRQOL between ICD and ONB in women. Methods: PubMed, Embase, and the Cochrane Library we searched for available papers published from inception up to December 2020. The outcomes were the score data from HRQOL questionnaires. The random-effects model was used for all analyses. Results: Four studies (six datasets; 283 patients) were included. In EORTC-QLQ-C30, there were no differences between ICD and ONB regarding cognitive functioning (WMD=1.18, 95%CI: -20.52,22.88, P=0.915), global health (WMD=1.98, 95%CI: -15.26,19.22, P=0.822), emotional functioning (WMD=0.86, 95%CI: -19.62,21.33, P=0.935), physical functioning (WMD=0.94, 95%CI: -11.61,13.49, P=0.883), role functioning (WMD=-4.94, 95%CI: -12.15,2.27, P=0.180), and social functioning (WMD=-4.71, 95%CI: -20.83,11.40, P=0.567). There were no differences between ONB and ICD for specific symptoms (fatigue, nausea and vomiting, and pain) and single items (dyspnea, insomnia, appetite loss, constipation, diarrhea, and financial difficulties) (all P>0.05). In EORTC-QLQ-BLM30, there were no differences between ICD and ONB regarding bowel symptoms (WMD=5.45, 95%CI: -15.30,26.20, P=0.607), body image (WMD=-13.12, 95%CI: -31.15,4.92, P=0.154), sexual functioning (WMD=-5.55, 95%CI: -14.96,3.85, P=0.247), and urinary symptom (WMD=5.50, 95%CI: -7.34,18.34, P=0.401), but one study reported better future perspective with ONB (WMD=-14.9, 95%CI: -27.14,-2.66, P=0.017) Conclusion: Women who underwent ONB do not appear to have a statistically significantly better HRQOL than women who underwent ICD, based on EORTC-QLQ-C30 and EORTC-QLQ-BML30.